2009
DOI: 10.1194/jlr.m800296-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

An altered pattern of circulating apolipoprotein E3 isoforms is implicated in preeclampsia

Abstract: Preeclampsia is a common pregnancy complication that is an important cause of preterm birth and fetal growth restriction. Because there is no diagnostic test yet available for preeclampsia, we used a proteomic approach to identify novel serum/plasma biomarkers for this condition. We conducted case control studies comparing nulliparous women who developed preeclampsia at 36-38 weeks of gestation with healthy nulliparous women matched by gestational age at sampling. Serum/plasma was depleted of six abundant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 50 publications
4
45
0
1
Order By: Relevance
“…The authors suggested these so-called "cargo proteins" to modify the anti-inflammatory properties of HDL and, thus, might be linked to the relationship between preeclampsia and later coronary artery disease. Interestingly, a recent proteome study of plasma proteins of a "late-onset subgroup" of preeclampsia revealed that transthyretin levels, besides other factors, were elevated compared with those from healthy pregnant controls [49].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested these so-called "cargo proteins" to modify the anti-inflammatory properties of HDL and, thus, might be linked to the relationship between preeclampsia and later coronary artery disease. Interestingly, a recent proteome study of plasma proteins of a "late-onset subgroup" of preeclampsia revealed that transthyretin levels, besides other factors, were elevated compared with those from healthy pregnant controls [49].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the well-known function of removal of excess cholesterol from the circulation via regulation of hepatic uptake (Belo et al 2004), its function also involves modification of inflammatory responses, including suppressing T cell proliferation, macrophage regulation, lipid antigen presentation facilitation (by CD1) to natural killer T cells, as well as modulation of inflammation and oxidation (Zhang et al 2010). Epidemiological studies have reported that increased levels of APOE are associated with an increased risk of pre-eclampsia, whereas genetic association studies suggested that polymorphisms in APOE are also associated with preeclampsia (Atkinson et al 2009) and spontaneous abortions in patients with endometriosis (Collazo et al 2012). In addition, APOE is involved in inflammatory pathways.…”
Section: Emergency Caesarean Sectionmentioning
confidence: 99%
“…Increased plasma apoE polymorphisms have been reported in women with pre-eclampsia (17,18), however findings relating to apoA1 measurements in pre-eclampsia are conflicting (19,20). To-date, it is not known whether AIBP is expressed in the placenta or altered in pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%